2016
DOI: 10.4103/0974-8490.182913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin anti-aging potential of Citrus reticulata blanco peel

Abstract: Background:The peel of Citrus reticulata Blanco is traditionally used as tonic, stomachic, astringent, and carminative. It is also useful in skin care.Objective:To study the anti-aging potential of alcoholic extracts of C. reticulata Blanco peel using in vitro antioxidant and anti-enzyme assays.Materials and Methods:Plant extracts were obtained by Soxhlation (CR HAE- Hot Alcoholic Extract of Citrus reticulata) and maceration method (CR CAE- Cold Alcoholic Extract of Citrus reticulata). Qualitative and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 22 publications
(22 reference statements)
0
28
0
2
Order By: Relevance
“…These results suggested that the chemical constituents in the extract may have antiaging properties via inhibiting elastase and delaying the degradation of elastin fibers. Previous studies reported that the plant extract and phytocompounds with good elastase inhibition activity such as white tea (89%), Citrus reticulate (80%), epigallocatechin gallate (84.79%), oleanolic acid (74.1%), and catechin (80.5%) can offer significant antiaging properties (Apraj & Pandita, ; Thring et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the chemical constituents in the extract may have antiaging properties via inhibiting elastase and delaying the degradation of elastin fibers. Previous studies reported that the plant extract and phytocompounds with good elastase inhibition activity such as white tea (89%), Citrus reticulate (80%), epigallocatechin gallate (84.79%), oleanolic acid (74.1%), and catechin (80.5%) can offer significant antiaging properties (Apraj & Pandita, ; Thring et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Gold lotion (GL), a formulated product extracted from the peels of six citrus fruits (navel oranges, Citrus hassaku , Citrus limon , Citrus natsudaidai , Citrus miyauchi Iyo and Satsuma), has been developed in Japan. GL contains various flavonoids that have potential to protect the skin against UV‐induced damage and aging . In addition to skin protection, GL has also been demonstrated to suppress azoxymethane‐induced aberrant crypt foci formation in mice by downregulating inflammation‐related protein levels that may subsequently prevent inflammation‐associated colon tumorigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…23,24 One of the most common method for testing preliminary antioxidant activity of plant extracts is DPPH radical-scavenging. 25 In this test, the antioxidant activity of S. plagyophyllum extract (50 mg/mL) was 41,61±0,02% (E1), 39,16±0,01% (E2), 37,58±0,03% (E3) and ascorbic acid 78.03±0,65 % (22.44 µg/mL) as antioxidant activity comparison (Figure 3.). Extract ethanol 25% of S. plagyophyllum had the highest antioxidant activity than other extract.…”
Section: Discussionmentioning
confidence: 86%